Cultural Adaptation and Retention : The Narrative Tradition of the African-Caribbean Community of Toronto - Butler, Gary (Ethnologies, 1996)
This article discusses strategies for cultural maintenance and adaptation as revealed through an analysis of oral narrative performances among members of Toronto’s African-Caribbean community. Issues related to ethnic and linguistic identification in a contemporary multicultural society are examined in terms of “socialization and secondary enculturation processes” and, more specifically, in the light of traditional folktale material as transmitted in a new setting, to a new generation. The research involved was carried out with funding from the Government of Canada and York University.